Methodology Of Individualization Of Physical Loads Based On Monitoring The Functional State Of Students (Journal of Pedagogical Inventions and Practices, 2026)
The article examines the problem of funksional monitoringga tayangan individual yuklama metodikasi within the framework of sport pedagogy, physical culture theory and health-oriented higher education. The relevance of the study is determined by the need to transform physical education from a predominantly normative lesson into a pedagogical environment that develops health literacy, independent exercise habits, movement safety, social interaction and self-regulation. The object of the research is talabayoshlarning yurak-qon tomir, nafas olish, mushak chidamliligi, koordinatsion tayyorgarlik va tiklanish ko‘rsatkichlari; the subject is mashg‘ulot yuklamasini yurak urish tezligi, subyektiv zo‘riqish, test natijalari va tiklanish belgilariga qarab moslashtirish metodikasi. On the basis of theoretical analysis, comparative pedagogical generalization and model design, the article proposes kirish diagnostikasi, haftalik monitoring, yuklama zonalarini belgilash, xavf belgilarini nazorat qilish, mikrotsiklni tuzatish va yakuniy refleksiv baholashdan iborat individualizatsiya algoritmi. The scientific novelty is connected with talabalarning jismoniy tayyorgarligini bir xil normativlar bilan emas, balki funksional holat dinamikasini aks ettiruvchi ko‘p mezonli monitoring orqali baholash va shu bahoga mos mashg‘ulot trayektoriyasini qurish. The results clarify the structural components, pedagogical conditions and expected educational effects of the proposed approach. The practical value lies in the possibility of using the model in higher education institutions for lesson planning, differentiated workload management, student reflection and sustainable physical activity promotion